2002
DOI: 10.1093/cercor/12.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Early Cortical Distinction between Memories that Pertain to Ongoing Reality and Memories that Don't

Abstract: Patients with anterior limbic lesions, in particular of the posterior orbitofrontal cortex, often act on the basis of memories that do not relate to ongoing reality and justify their behavior with invented stories that can mostly be traced back to real events (spontaneous confabulation). Recent studies demonstrated that the patients fail to suppress activated memory traces that do not pertain to ongoing reality. In the present study, we used a similar paradigm and high-resolution event-related potentials to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
79
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 56 publications
12
79
1
Order By: Relevance
“…Studies using surface EEG had shown late-amplitude differences over temporal or parietal scalp electrodes (Friedman, 1990;Schnider et al, 2002;Kayser et al, 2003). According to spatiotemporal analyses, however, these amplitude differences appeared in the context of similar electrocortical patterns and hence reflected amplitude modulation of similar cortical networks rather than different generators (Schnider et al, 2002;James et al, 2009). The present findings obtained with depth electrodes confirm the latter interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using surface EEG had shown late-amplitude differences over temporal or parietal scalp electrodes (Friedman, 1990;Schnider et al, 2002;Kayser et al, 2003). According to spatiotemporal analyses, however, these amplitude differences appeared in the context of similar electrocortical patterns and hence reflected amplitude modulation of similar cortical networks rather than different generators (Schnider et al, 2002;James et al, 2009). The present findings obtained with depth electrodes confirm the latter interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying orbitofrontal reality filtering appears to be similar to extinction capacity, the ability to abandon anticipations that are no longer valid (Nahum, Ptak, Leemann, & Schnider, 2009). Recent studies have shown that this process is rapid (200-300 ms after stimulus presentation; Schnider, Valenza, Morand, & Michel, 2002), and that it dissociates from other memory control processes like context source memory (BouzerdaWahlen, Nahum, Liverani, Guggisberg, & Schnider, 2014;Johnson, Kounios, & Nolde, 1997;Mitchell & Johnson, 2009), strategic retrieval monitoring (BouzerdaWahlen, Nahum, Ptak, & Schnider, 2013;Gilboa et al, 2006;Wahlen, Nahum, Gabriel, & Schnider, 2011) and temporal order memory (Liverani et al, 2015). These processes are laborious and have different signatures in evoked potential studies (Bouzerda-Wahlen et al, 2014;Liverani et al, 2015;Wahlen et al, 2011).…”
mentioning
confidence: 99%
“…Finally, the extinction task used in this and our previous study (Nahum et al, 2009 ) requires explicit, conscious decisions. It is, therefore, unlikely to be a perfect measure of the pre-conscious process that reality fi ltering seems to be (Schnider et al, 2002 ). Nonetheless, the construction of tasks attempting to test theories of confabulation is crucial for future progress.…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tomography studies with healthy subjects performing adapted versions of the same task demonstrated activation of the posterior orbitofrontal cortex (area 13) (Schnider, Treyer, & Buck, 2000 ) and subcortical loops (Treyer, Buck, & Schnider, 2003 ). An evoked potential study indicated that the correct judgment of items as not-pertaining-to-now (the avoidance of false positive responses) occurs at an early stage of processing, at approximately 200-300 ms, before processes of (conscious) recognition and re-encoding set in (Schnider, Valenza, Morand, & Michel, 2002 ). Based on these fi ndings, the reality fi lter hypothesis holds that the reality confusion characterizing behaviorally spontaneous confabulation emanates from the failure of a preconscious orbitofrontal mechanisms that suppresses the interference of memories that do not pertain to ongoing reality (Schnider, 2008 ).…”
Section: Symposiummentioning
confidence: 99%
See 1 more Smart Citation